Tensile and viscoelastic characterization of magnetorheological elastomers with varying carbonyl iron particle concentration - Mohd Fauzi Mohd Yunus; Izwan Ismail; Syarifah Nur Aqida Syed Ahmad (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2026)
Magnetorheological elastomers (MREs) are smart composite materials whose mechanical properties can be tuned under magnetic fields, making them ideal for adaptive vibration control. This study examines the viscoelastic behavior of MREs containing 0%, 10%, 20% 30%, 40% and 50% carbonyl iron particles (CIPs) through uniaxial tensile testing. Key mechanical parameters, including tensile stress at 0.2% strain, modulus, and load at yield, were evaluated across twelve samples. The storage modulus was determined using both Rubber Elasticity Theory and the Maxwell–Kelvin viscoelastic model to compare their predictive accuracy. Results revealed that the storage modulus increased with CIP content up to 30% (1.5 MPa, Rubber Elasticity Theory) before slightly declining at 50% (0.6 MPa), likely due to particle agglomeration. The Rubber Elasticity Theory consistently predicted higher moduli than the Maxwell–Kelvin model. Qualitatively, damping improved with higher CIP content, indicated by greater load at yield. These findings highlight the crucial role of filler concentration in tailoring MRE stiffness and damping performance, while emphasizing the need for dynamic mechanical testing to validate energy dissipation mechanisms. The study provides insights into optimizing MRE formulations for engineering applications such as vibration isolation and adaptive control systems.